2019
DOI: 10.1016/j.aott.2019.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Locally administrated single-dose teriparatide affects critical-size rabbit calvarial defects: A histological, histomorphometric and micro-CT study

Abstract: ObjectiveThe aim of this study was to evaluate the effect of teriparatide (PTH 1-34, rhPTH) on a rabbit defect model with local xenogen grafts histomorphometrically and radiologically.MethodsFor this purpose, two 10 mm diameter critical-size defects were created in the calvaria of 16 rabbits. In the control group, the defect area was filled with a xenogen graft, while in the teriparatide group (PTH 1-34), a xenogen graft combination with 20 mcg teriparatide was used. For both 4 – week and 8 – week study groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Studies have shown that the local use of teriparatide intermittently and subcutaneously resulted in an increase in the amount of newly formed bone tissue [ 38 , 56 ]. Ozer et al [ 42 ] also addressed the local use of teriparatide with xenografts in rabbits and found that in periods of 4 and 8 weeks, the group with the presence of the drug showed higher mean values of new bone formation. However, these values were greater in the period of 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that the local use of teriparatide intermittently and subcutaneously resulted in an increase in the amount of newly formed bone tissue [ 38 , 56 ]. Ozer et al [ 42 ] also addressed the local use of teriparatide with xenografts in rabbits and found that in periods of 4 and 8 weeks, the group with the presence of the drug showed higher mean values of new bone formation. However, these values were greater in the period of 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the association between bioglass particles and local medicines for osteoporosis in the in vivo response, the choice of this drug was due to its favorable effects on bone tissue metabolism [ 39 , 40 , 42 , 43 ] and evidence in the literature on its effect on cell cultures [ 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…45 However, PTH systemic administration drawbacks include the need for daily/weekly self-injections, the exposure of not-target areas, and mild side-effects. 46 Although, literature is scarce regarding the effects of local application of PTH, a handful of pre-clinical studies in calvaria 34,[47][48][49] and femoral defects 33 of small rodents have offered interesting results for bone regeneration with the association of PTH and bone grafting materials. Özer et al 48 reported that the association of xenografts with 20 μg of PTH produced a significant increase in new bone formation in critical calvaria defects at 8 weeks regarding defects treated only with xenografts.…”
Section: Discussionmentioning
confidence: 99%
“…46 Although, literature is scarce regarding the effects of local application of PTH, a handful of pre-clinical studies in calvaria 34,[47][48][49] and femoral defects 33 of small rodents have offered interesting results for bone regeneration with the association of PTH and bone grafting materials. Özer et al 48 reported that the association of xenografts with 20 μg of PTH produced a significant increase in new bone formation in critical calvaria defects at 8 weeks regarding defects treated only with xenografts. Kajii et al 47 reported similar results, with the combination of an octacalcium phosphate and collagen composite with 1.0 or 0.1 μg of PTH, where histomorphometric analysis evidenced enhanced bone regeneration in calvaria critical defects with the use of PTH compared to the control group, regardless of PTH concentration.…”
Section: Discussionmentioning
confidence: 99%